Ալեսսանդրո Մանձոնիի «Նշանվածները» («Ֆերմո և Լուչիա») պատմավեպի առանձնահատկությունները - Աննա Հարությունյան (ՀՀ ԳԱԱ հրատ.)
Роман Алессандро Мандзони «Обрученные», будучи первым историческим романом в итальянской литературе, находит широкое распространение и становится не только ярким примером для итальянских авторов, но и основой для продолжения развития итальянской литературы в новом направлении и по–новому. The “Betrothed Lovers”, a novel by Alessandro Manzoni, being the first historical novel of Italian literature, being the first historical novel in Italian literature, was widespread and not only a vivid example for Italian authors, but also the basis for the continuing development of Italian literature in a new direction.
Keywords: Language and Literature; Literature